Electrophoretic deposition of hydroxyapatite‐shrimp crusts nanocomposite thin films for bone implant studies. Issue 6 (23rd April 2018) - Ismail, Raid A.; Hamoudi, Walid K.; Abbas, Hadeel F.
Abstract : Hydroxyapatite‐shrimp crusts nanocomposite thin films were deposited on titanium substrates by electrophoretic technique, under different preparation conditions, for bone implant applications. Fourier transform infrared spectrometer, atomic force microscope, X‐ray diffraction (XRD), optical microscope, and scanning electron microscope were employed to characterise the synthesised films. Vickers' micro‐hardness measurements revealed a value of 502 HV for the hydroxyapatite films and 314.55 HV for the nanocomposite films. XRD results confirmed the polycrystalline nature of the hydroxyapatite and hydroxyapatite‐shrimp nanocomposite films. The in‐vitro bioactivity test of the synthesised films in simulated body fluid showed very low dissolution rate. Antibacterial activity of synthesised films was investigated against E. coli bacteria.